Knowledge, opinions, and practices about oral cancer among general medical practitioners in Lagos, Nigeria - Olalekan Micah Gbotolorun; Olutola Eweka; Akinola Lawal; Olurotimi Fadeyibi; Christian Ibezie Emeka (Wolters Kluwer Medknow Publications, 2015)
Objectives: To evaluate the knowledge and practices of general medical practitioners (GMPs) in Lagos on screening for oral cancer (OC). Materials and Methods: A 43-item self-administered questionnaires was filled by each GMPs recruited into the study. Analysis was done using the SPSS version 17.5. Descriptive analyses were used and results were presented in percentages, graphs, and tables. Results: One-hundred and twenty GMPs participated in the study, 58.7% were males and 41.3% females; their ages ranged 22-61 years (36.1 ΁ 7.97). While most participants answered correctly that smoked tobacco (96.1%), increasing age >45 years (97%), oral sex (99%), and patient with a previous OC (93.7%) were risk factors for OC; there was misinformation on the nonrisk factors as only 5.5%, 7.9%, and 18.9%, respectively, answered correctly that family history of cancer, dental infections, and poor oral hygiene were not identifiable risk factors associated with OC. Furthermore, although majority of subjects (81.1%) identified the floor and the tongue as the most common sites of OC and leukoplakia (75.6%) as a common precursor of OC; only 29.1% identified correctly that OC had one of the worst morbidity and mortality rates of the most common cancers due to late presentation. Only 0.8% of GMPs had a consistent high score in the indexes. Conclusion: The knowledge and practices of GMPs in the Lagos environment on OC needs a lot of improvement for them to become significant in the screening for the disease entity.